Energy efficiency and heating technology investments: Manipulating financial information in a discrete choice experiment - Lang, Ghislaine; Farsi, Mehdi; Lanz, Bruno; Weber, Sylvain (Resource and energy economics, 2021)
•Homeowners value energy efficiency beyond expected heating cost savings.•They have strongly heterogeneous preferences for different heating technologies.•Fossil fuel users are not willing to pay required premiums for low-carbon options.•Targeted subsidies combined with information can help phasing out fossil fuels. We elicit homeowners’ willingness to pay (WTP) for energy efficiency and low-carbon technologies in the context of heating appliance replacement. We employ a within-between subject design that involves manipulating information in a two-stage discrete choice experiment (DCE) and use WTP space estimation to identify the role of financial information in reducing fossil fuel use. We find that homeowners’ average valuation of energy efficiency exceeds associated heating cost savings, suggesting that they also consider non-monetary benefits when evaluating this type of investment, whereas information about private and pro-social benefits of investments only has a limited impact on WTP. Evidence also suggests that homeowners have a strong preference for the existing technology. Consequently, fossil fuel users’ WTP for switching to low-carbon technologies does not cover respective investment cost differentials, and we derive evidence on how combined subsidies and information can induce these users to opt out of fossil technologies.